Integrating EcoVadis into healthcare sustainability practices : a focus on medical waste management at a private hospital group in Vietnam - Phan Thi Bao Chau; Shah, Faiz H.; Levermore, Roger; Galipeau, David (Pathumthani,Thailand : Asian Institute of Technology, 2025)
This thesis explores the integration of the EcoVadis framework into healthcare sustainability, with a focus on medical waste management at a Vietnamese private hospital group. Using a mixed-methods approach, the study evaluates quantitative waste KPIs and qualitative insights from staff interviews, structured around seven EcoVadis indicators: Policies (POLI), Endorsements (ENDO), Measures (MESU), Certifications (CERT), Coverage (COVE), Reporting (REPO), and 360° Watch Findings (360). Findings reveal strong internal waste management systems, regulatory compliance, and alignment with Joint Commission International (JCI) standards. However, gaps exist in external reporting, sustainability certifications, and policy standardization across hospital sites. Waste generation rates are higher than optimal benchmarks, emphasizing the need for enhanced waste reduction strategies. Reporting remains largely internal and ad hoc, driven by EcoVadis assessments rather than public disclosures. The study recommends expanding external sustainability reporting, improving policy cohesion, strengthening ESG commitments, and leveraging JCI{u2019}s evolving sustainability criteria. By illustrating how EcoVadis can support healthcare sustainability, this research provides a scalable framework for hospital administrators and policymakers. Future studies should examine long-term ESG adoption, inter hospital benchmarking, and the role of technology in sustainable healthcare management.
A project report submitted in partial fulfillment of the requirements for the degree of Professional Master in ESG (Environment-Social-Governance) Management
Keywords: Hospitals -- Vietnam -- Waste disposal; Hazardous Waste -- Vietnam -- Environment aspects